La fruizione inclusiva nel progetto di restauro: il caso degli anfiteatri romani Percorsi di conoscenza e indirizzi metodologici - CAPPELLI, LUIGI (People_Places_Architecture, 2023)
Roman amphitheatres are an interesting field of investigation and allow to analyze and classify structural instability, recurrent forms of degradation and anomalies related to their accessibility. These critical issues emerge, in particular, from the study of two interesting case studies, the Roman Amphitheatre in Tarragona, Spain, and the Roman Amphitheatre of Santa Maria Capua Vetere, Italy. Through a contextual interpretation of literary, historiographic and iconographic testimonies, in the light of the expertise of architectural restoration and an in situ cognitive campaign supported by surveys, the main theoretical and design nodes connected to the restoration and enhancement of these monumental complexes are identified: knowledge, conservation, use and management, understood as scheduled maintenance and constant monitoring.